Explanation:
f(x) = x^4 -x^2 +9
g(x) = x^3 +3x^2 +12
We are subtracting
f(x) -g(x) =x^4 -x^2 +9 - ( x^3 +3x^2 +12)
Distribute the minus sign
x^4 -x^2 +9 - x^3 -3x^2 -12
I like to line them up vertically
x^4 -x^2 +9
- x^3 -3x^2 -12
-------------------------
x^4 -x^3 -4x^2 -3
2. a1 = -7.4
To find the common difference, take term 2 and subtract term 1
-21.2 - (-7.4)
-21.2 + 7.4
-13.8
an = an-1 -13.8
if you need anymore help just ask and if you wondering i found another question which its the same one as this one so her it is